Peningkatan Kualitas Infrastruktur Permukiman Melalui Pemberdayaan Masyarakat Desa/Kelurahan Berbasis Data Base Digital Keruangan (SPASIAL) Di Kabupaten Wajo - Abdul Rachman Rasyid; Andi Lukman Irwan; Laode Muhammad Asfan Mujahid; Ihsan -; Mimi Arifin; M. Yahya; Firman Husain (Faculty of Engineering UNHAS, 2019)
Wajo Regency is one of the districts that have a role in the development and progress of South Sulawesi Province. Therefore, agricultural production facilities will be developed through processing mechanisms to the creative industries. Irrigation will be directed at the development of large-scale and small-scale rural irrigation through artificial embankments, revitalization of swamps and lakes. Whereas in urban areas a residential environment will be held an adjustment, especially near the of Lake Tempe in the area of ​​Sengkang as the Capital of Wajo Regency. The purpose of this study is to find easy access for the community to drinking water and to provide accurate data related to Geographic Information System (GIS)-based regional location conditions. The approach used in this activity is a field survey related to the existing condition of the location by assisting the community, increasing knowledge by training or counseling aimed at solving existing problems in the village / subdistrict in Tempe Subdistrict, Wajo Regency, as well as training and utilizing digital databases related to the profile and potential of the city. The results of the study obtained were that some districts had several problems, namely, solid waste systems, road networks, inadequate buildings and inadequate clean water especially in Attakae, Maddukelleng, Pattirosompe and Tempe. However, there is potential that can be developed to improve the regional economy, such as the silk industry and wood industry.